Fiscalização difusa da constitucionalidade e o incidente de argüição de inconstitucionalidade - Pogliesse, Marcelo Weick (2006)
The present work consists of studying to diffuse control of constitutionality in Brazil, with emphasis in a procedural alternative to the evolution of that model: the incident to challenge of unconstitutionality. Starting from the discussion about the new role of constitutional jurisdiction in peripheral countries and in the globalized society, without forgetting to face inevitable doubts about its legitimacy before other powers of the State, the Brazilian control of constitutionality is revealed, under a diffuse, non-dichotomical view, through a number of inconsistencies and misunderstandings, that compromise social peace, the credibility of democratic institutions and the supremacy of juridical security. In order to achieve the goal, the study in course discussed the main difficulties of the Brazilian mixed model of constitutionality control, as well as, directing its view to the incident of challenge of unconstitutionality, which the most adequate forms to assure its appropriateness, legitimacy, processing and decisory effects are. Is was essential, in this point of view, to establish the difference between the incident of challenge of unconstitutionality conceived in article of the Brazilian Federal Constitution and the incident of challenge of unconstitutionality such as it is known in the European models. The insertion of the incident of challenge of unconstitutionality based on European models in the Brazilian control system, without jeopardizing the North-American essence the Brazilian constitutional history presents since 1981, is the hypothesis that is presented as an improvement of constitutional protection